Let's solve each equation to find their respective solutions:
-
16x = 64
- Divide both sides by 16: \[ x = \frac{64}{16} = 4 \]
-
x/4 = -1
- Multiply both sides by 4: \[ x = -1 \times 4 = -4 \]
-
-12x = 48
- Divide both sides by -12: \[ x = \frac{48}{-12} = -4 \]
-
x - 2 = 2
- Add 2 to both sides: \[ x = 2 + 2 = 4 \]
Now, let's summarize the solutions:
- For \( 16x = 64 \), the solution is \( x = 4 \).
- For \( \frac{x}{4} = -1 \), the solution is \( x = -4 \).
- For \( -12x = 48 \), the solution is \( x = -4 \).
- For \( x - 2 = 2 \), the solution is \( x = 4 \).
The equations that yield the same solutions are:
- \( 16x = 64 \) leads to \( x = 4 \).
- \( -12x = 48 \) leads to \( x = -4 \).
- \( x - 2 = 2 \) leads to \( x = 4 \).
- \( \frac{x}{4} = -1 \) leads to \( x = -4 \).
The equation with a different solution is x/4 = -1 because it results in \( x = -4 \), while the others yield \( x = 4 \).